Genetic Analysis of Autosomal Short Tandom Repeats Loci in The Libyan Western Mountain Population - Refaat Tabagh; Asma Abuallag; Mohamed Marwan; Mohamed Al-Griw (AlQalam Journal of Medical and Applied Sciences, 2024)
There is a little investigation of the genetic diversity of the Libyan population. This study aimed to explore STR loci in the Libyan western mountain population to analyse its genetic landscape. Allele frequency for 15 autosomal STR loci (D8S1179, D21S11, D7S820, CSF1PO, D3S1358, THO1, D13S317, D16S539, D2S1338, D19S433, VWA, TPOX, D18S51, D5S818, FGA) included in the Identifiler®Plus kit were investigate in 120 random unrelated individuals from the Westerner Mountain area of Libya. No deviations from Hardy-Weinberg equilibrium were seen, with the exception of D8S1179, D21S11, D3S1358, TH01 and FGA loci. A total of 129 alleles were observed with the corresponding allelic frequencies ranging between 0.00417 and 0.47917 of the studied sites were observed, and that alleles 8 and 12 are the highest frequency for all studied areas for the TPOX and D5S818 sites respectively had a value of (0.47917). D18S51 was also observed to be the most diverse site (Expected heterozygosity: 0.88312 and probability of matching: 0.0354). The results indicate that the 15 STR loci have a significant genetic diversity among studied individuals and are suitable for personal identification in the criminal field, and the importance of this work lies in the creation of a database of frequency distribution of allelic frequencies to be used for criminal identification, identification of missing persons and paternity tests. هناك القليل من البحث في التنوع الجيني للسكان الليبيين. تهدف هذه الدراسة إلى استكشاف مواضع التكرار الترادفية القصيرة في سكان الجبال الغربية الليبية لتحليل المشهد الجيني الخاص بهم. تم التحقيق في تردد الأليل لـ 15 موضعًا جسميًا متكررًا قصيرًا (D8S1179 و D21S11 و D7S820 و CSF1PO و D3S1358 و THO1 و D13S317 و D16S539 و D2S1338 و D19S433 و VWA و TPOX و D18S51 و D5S818 و FGA) المضمنة في مجموعة Identifiler®Plus في 120 فردًا عشوائيًا غير مرتبطين من منطقة الجبال الغربية في ليبيا. لم يتم ملاحظة أي انحرافات عن توازن هاردي وينبرج، باستثناء مواضع D8S1179 و D21S11 و D3S1358 و TH01 و FGA. وقد تم رصد 129 جينًا إجمالاً بترددات أليلية مقابلة تتراوح بين 0.00417 و0.47917 من المواقع المدروسة، وأن الأليلين 8 و12 هما أعلى تردد لجميع المناطق المدروسة لمواقع TPOX وD5S818 على التوالي بقيمة (0.47917). كما لوحظ أن D18S51 هو الموقع الأكثر تنوعًا (التغاير المتوقع: 0.88312 واحتمال المطابقة: 0.0354). تشير النتائج إلى أن مواقع STR الـ 15 لديها تنوع وراثي كبير بين الأفراد المدروسين وهي مناسبة للتعريف الشخصي في المجال الإجرامي، وتكمن أهمية هذا العمل في إنشاء قاعدة بيانات لتوزيع الترددات الأليلية لاستخدامها في التعريف الجنائي وتحديد الأشخاص المفقودين واختبارات الأبوة